Cross-border tourist mobility as seen by residents of the Karelian borderlands: COVID-19 restrictions - Kondrateva, S. V. (Baltic Region, 2023)
This article offers a new approach to evaluating the significance of cross-border tourism for residents of the border region of Karelia amid COVID-19 restrictions. The work draws on data of a municipal-level survey of the region’s population (575 people), conducted by the author in collaboration with Dr Ekaterina Shlapeko in 2021. Analysis of the survey results has confirmed the customariness of cross-border tourist mobility for the Karelians and the essential role it plays in their lives. These are manifested in regular trips to the neighbouring state, frequent contacts with Finnish travellers, marked preferences and a network of contacts with Finnish residents and organisations. The COVID-19 restrictions affected the routines of the residents of the Karelian borderlands more severely than those of people living in the inner municipalities or the regional capital. The findings of the study provide a comprehensive picture of the significance of cross-border tourist mobility (border tourism) and point to spatial differences in the perception of the study phenomenon by the residents of border, interior and urban municipalities. When applied in practice, the proposed approach gives an opportunity to widen the range of possible administrative decisions and can serve as a tool of regional economic policy on tourism.